Records in contexts: the road of archives to semantic interoperability. Issue 4 (7th November 2017) - Llanes-Padrón, Dunia; Pastor-Sánchez, Juan-Antonio
Abstract : Purpose: The purpose of this paper is to examine the Records in Contexts proposal of a conceptual model (RiC-CM) from the International Council on Archives' (ICA) archival description and to propose an OWL ontology for its implementation in the semantic web. Design/methodology/approach: The various elements of the model are studied and are related to earlier norms in order to understand their structure and the modeling of the ontology. Findings: The analysis reveals the integrating nature of RiC-CM and the possibilities it offers for greater interoperability of data from archival descriptions. Two versions of an OWL ontology were developed to represent the conceptual model. The first makes a direct transposition of the conceptual model; the second optimizes the properties and relations in order to simplify the use and maintenance of the ontology. Research limitations/implications: The proposed ontology will follow the considerations of the final version of the ICA's RiC-CM. Practical implications: The analysis affords an understanding of the role of RiC-CM in publishing online archival data sets, while the ontology is an initial approach to the semantic web technologies involved. Originality/value: This paper offers an overview of Records in Contexts with respect to the advantages in the field of semantic interoperability, and supposes the first proposal of an ontology based on the conceptual model.